Autoinflammatory Diseases (AID) - Dueckers, G.; Sander, O.; Niehues, T. (Klinische Pädiatrie, 2014)
Most of the autoinflammatory diseases (AID) are orphan diseases with recurrent episodes of systemic inflammation. Fever and exanthema are leading features. Given the ongoing elucidation of pathogenic causes and hence therapeutic approaches, we provided a review of the current literature of AID.
Keywords: autoinflammatory diseases; monogenetic; inflammasome; interleukin 1